A Source of Hope Whilst in Waiting: The Contributions of Religiosity to the Psychological Well-Being of Involuntarily Single Women: [Sumber Pengharapan dalam Penantian: Kontribusi Religiositas terhadap Kesejahteraan Psikologis pada Perempuan Lajang yang Ingin Menikah] - Lianda, Talent Christabel Raissa; Himawan, Karel Karsten (ANIMA Indonesian Psychological Journal, 2022)
This study took as its start-off point, in the context of a patrilineal society, that being religious is evaluated as being a positive matter, and that not yet being married is evaluated as being negative and attracting stigma. The goal of the study was to explore the role of religiosity in the well-being of involuntarily single women in Indonesia. The religiosity of the participants was measured using The Four Basic Dimensions of Religiousness Scale (4-BDRS) and their psychological well-being by using the Satisfaction with Life Scale (SWLS). Through a technique of purposive sampling, a total of 169 female participants (Mage = 29.11; SD = 3.41) took part in an online survey. The results of regression analysis showed the existence of a meaningful role for religion, in the psychological well-being of involuntarily single women. Involuntarily single women who were active in religious activities tended to have higher levels of psychological well-being. The use of simple regression data analysis and statistical testing indicated that there was a pattern of religiosity specific to individuals across religious groups. It is hoped that this study might provide valuable views, particularly for Indonesian society, the portion of whose citizens who have not yet married is experiencing an increase. Studi ini mengambil titik tolak dalam konteks masyarakat patrilineal, ketika menjadi religius dinilai positif dan belum menikah dinilai negatif dan berstigma. Tujuan studi ini adalah mengeksplorasi peran religiositas terhadap kesejahteraan individu perempuan lajang yang ingin menikah di Indonesia. Religiositas partisipan diukur dengan menggunakan The Four Basic Dimensions of Religiousness Scale (4-BDRS) dan kesejahteraan psikologis diukur dengan menggunakan Satisfaction with Life Scale (SWLS). Dengan teknik purposive sampling, total sebanyak 169 partisipan perempuan (Musia = 29,11; SD = 3,41) telah berpartisipasi dalam survei daring. Hasil analisis regresi menunjukkan adanya peran religiositas yang bermakna dalam kesejahteraan psikologis perempuan lajang yang ingin menikah. Perempuan lajang yang ingin menikah yang aktif pada aktivitas religius cenderung memiliki kesejahteraan psikologis yang lebih tinggi. Penggunaan teknik analisis data regresi sederhana serta uji statistik menunjukkan bahwa ada pola religiositas yang khusus pada individu, lintas kelompok agama. Studi ini diharapkan dapat memberikan wawasan berharga, khususnya bagi masyarakat Indonesia yang proporsi penduduk belum menikahnya terus mengalami peningkatan.